تطوير اللغز الرقمي لمادة التطبيق الصرفي 1 على الهاتف المحمول كالتدريبات الإضافية خارج الفصل الدراسي - Moh Fery Fauzi (Buletin Al-Turas, 2019)
Abstract: This research is generally aimed on producing a cellphone-based digital learning quiz for Tathbiq Sharfi I course in Arabic Department, Faculty of Letters, State University of Malang. Specifically, this research aimed at describing (1) the characteristic of a cellphone-based digital learning quiz for Tathbiq Sharfi I course, (2) degree of properness of a cellphone-based digital learning game for Tathbiq Sharfi I course, (3) the model of using of a cellphone-based digital learning quiz for Tathbiq Sharfi I course. The development of this media is using Sadiman & Rahardjo’s development design. The data collection is done by observation and giving questionnaire. The softwares used on developing this media are adobe flash CS 3, action script 2, and flash player. Based on the scoring by the material expert, it is known that this digital learning quiz is highly valid. Meanwhile, based on the scoring done by the media expert, the result shows that this digital learning game is valid to use. On the small-group tryout, it is known that this digital learning game is highly valid, and the field test also shows that this digital learning game is highly valid to use. Therefore, this cellphone-based digital learning game for Tathbiq Sharfi I course is highly valid to be used.Keywords: Digital Quiz, Cellphone, Learning Tathbiq Sharf I